Nephrosplenic space closure significantly decreases recurrent colic in horses: a retrospective analysis. (30th November 2019) - Arévalo Rodríguez, José Manuel; Grulke, Sigrid; Salciccia, Alexandra; de la Rebière de Pouyade, Geoffroy
Abstract : Background: Nephrosplenic space closure is commonly used to reduce relapse of nephrosplenic space entrapment in cases of left dorsal displacement of the left colon (LDDLC). Nevertheless, studies documenting the effectiveness of this surgery are sparse in the literature. The aim of this study was to analyse clinical data of horses presented for LDDLC and evaluate the effect of nephrosplenic space closure on the incidence of colic recurrence. Methods: Medical records of 156 horses diagnosed with LDDLC at the Equine Clinic of the University of Liège between 2004 and 2016 were retrieved for analysis. Extracted data included horse breed, sex, age and weight, initial treatment, and if a subsequent preventive surgical closure of the nephrosplenic space was carried out or not. Follow‐up information was obtained by telephone interview. Statistical analyses were performed using a chi‐squared test with significance set at P<0.05. Results: Follow‐up data were available for 65 per cent of horses. The mean follow‐up was 35 months. There was a significant decrease in the total incidence of colic after closure surgery compared with non‐operated horses. No horse was diagnosed with LDDLC after closure of the nephrosplenic space. Conclusion: Closure of the nephrosplenic space significantly decreases recurrent colic in horses compared with non‐operated horses.